PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, TIPE INDUSTRI DAN LIKUIDITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014 – 2016) - Diar Aprilliana Anggraeni, 14.05.52.0282; Aini, Nur (Students' Journal of Accounting and Banking, 2018)
This study examines and analyzes the influence of Profitability, Company Size, Leverage, Type of Industry, and liquidity on Corporate Social Responsibility Disclosure. The population in this study in the manufacture companies which are listed in Indonesia Stock Exchange in years 2014 until 2016. The samples selections are using purposive sampling with period of research year 2014 until 2016. Analyzes influence between variable by using method of multiple linear regression analysis. The result of this study indicate that profitability and type of industy has a significant positive effect on the Corporate Social Responsibility Disclosure, while company size, leverage and liquidity do not affect the disclosure of Corporate Social Responsibility Keywords: Corporate Social Responsibility Disclosure , Profitability, Company Size, Leverage, Type of Industry and Liquidity